2015
DOI: 10.4149/bll_2015_086
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of symptoms after catheter ablation of atrial fibrillation

Abstract: The aim of our study was to verify the effi ciency of catheter ablation of atrial fi brillation (CA AF) according to the "atrial fi brillation (AF) burden"(time spent in AF) and symptoms related to AF. METHODS: We retrospectively analysed a selected set of 133 patients with atrial fi brillation (81% men, 19% women) who underwent an invasive therapy in the form of CA AF and at the same time had an implanted longterm ECG loop recorder (Reveal XT) in a period of eight years. We investigated AF burden and objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…19 ). Finally, monitoring with ILR has an advantage of continuous application for a much longer time 14,[20][21][22][23][24] . However; limited memory for real ECG data with storing of overwritten files as frequency histograms has been only partly solved by implementing once-a-day automatic transtelephonic data transmission specifically in asymptomatic patients who may not activate transfer of all necessary ECG recordings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 ). Finally, monitoring with ILR has an advantage of continuous application for a much longer time 14,[20][21][22][23][24] . However; limited memory for real ECG data with storing of overwritten files as frequency histograms has been only partly solved by implementing once-a-day automatic transtelephonic data transmission specifically in asymptomatic patients who may not activate transfer of all necessary ECG recordings.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that longer ECG monitoring can more effectively detect clinically unrecognized recurrent arrhythmias after apparently successful ablation [5][6][7][8][9][10][11][12][13][14] .Which mode of long-term ECG monitoring should be preferred in terms of efficacy, comfort, or costs is not clear. Following catheter ablation for paroxysmal AF, even intermittent self-terminating AF/ AT episodes if recurring in clinically significant quantity, should not be missed by continuous ECG monitoring based on principle of endless loop with automatic arrhythmia detection and trans-telephonic ECG transmission limited to a couple of weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Identifi cation of pulmonary vein ectopy as a trigger of AF (Haïssaguerre et al, 1998) became the corner-stone for rhythm control using pulmonary vein isolation (PVI) via catheter ablation (5). Preservation of sinus rhythm with catheter ablation has been reported in up to 70 % patients with paroxysmal and 50 % with persistent AF, so the proportion of patients with AF recurrence still remains relatively high (6). Several protective and risk factors were identifi ed (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This retrospective study included patients from two cohorts: the Reveal LINQ usability study (ClinicalTrials.gov identifier: NCT01965899), a multicenter single-arm clinical study, and clinical data derived from a single center with extensive experience in evaluating the long-term outcome of AF ablation by means of ICM (Bou Ezzeddine et al, 2015). The patients of both cohorts provided written informed consent, and the study protocols were reviewed and approved by the Human Research Ethics Committee of each participating institution.…”
Section: Patient Populationmentioning
confidence: 99%